2022
DOI: 10.1017/s0007485322000372
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of monotypic and mixed diets for development, population growth and predation capacity of Typhlodromus bagdasarjani (Acari: Phytoseiidae)

Abstract: We quantified the life table parameters and predation capacity of a generalist predatory mite, Typhlodromus bagdasarjani Wainstein and Arutunjan on five monotypic diets, including Tetranychus urticae Koch (TSSM) eggs in the presence (SW) and absence (SN) of webs, Trialeurodes vaporariorum Westwood (GHWF) eggs (G), honeydew (H), and maize pollen (M) as well as three mixed diets, including SN + M, SN + G, and G + M. Our results showed that the individuals fed on the mixed diets had a considerably shorter develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…putrescentiae was added to the cattail pollen (a mixed diet). Mortazavi et al (2023) showed that the individuals of the generalist predatory mite, Typhlodromus bagdasarjani Wainstein & Arutunjan when fed on the mixed diets (pollen plus prey or prey plus prey) had a considerably higher population growth rate than those raised on the monotypic diets including prey or pollen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…putrescentiae was added to the cattail pollen (a mixed diet). Mortazavi et al (2023) showed that the individuals of the generalist predatory mite, Typhlodromus bagdasarjani Wainstein & Arutunjan when fed on the mixed diets (pollen plus prey or prey plus prey) had a considerably higher population growth rate than those raised on the monotypic diets including prey or pollen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pollen, some generalist predatory mites can feed on factitious prey include sterilized eggs of Ephestia kuehniella Zeller (Lepidoptera: Pyralidae), cysts of Artemia franciscana Kellogg (Branchiopoda: Artemiidae) (Vangansbeke et al 2014), and stored acarid mites (Pirayeshfar et al 2020, Yazdanpanah et al 2022a) that frequently used as an alternative diet alone, as a part of a mixed diet or as a factitious prey. On the other hand, diet mixing is common among generalist predatory mites, and positive effects of diet mixing on phytoseiids' performance have been documented (Nomikou et al 2003, Samaras et al 2019, Mortazavi et al 2023). Mixed diet including combination of two or several prey, combination of prey and pollen, and mixture of different pollen grains could enhance the biological control effectiveness because of the positive effects of this diet type on the numerical response of the predators (Delisle et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The generalist phytoseiids can feed on mites of different families, insect species (Gerson & Weintraub 2012; Mortazavi et al . 2019), nectar (van Rijn & Tanigoshi 1999), honeydew (Mortazavi et al . 2023), mildew (Zemek & Prenerova 1997), and pollen (van Rijn & Tanigoshi 1999; Eini et al .…”
Section: Introductionmentioning
confidence: 99%
“…The generalist phytoseiids can feed on mites of different families, insect species (Gerson & Weintraub 2012;Mortazavi et al 2019), nectar (van Rijn & Tanigoshi 1999, honeydew (Mortazavi et al 2023), mildew (Zemek &Prenerova 1997), andpollen (van Rijn &Tanigoshi 1999;Eini et al 2022). This great diversity of feeding habits permits their survival and reproduction by feeding on various food sources including different pollen types in the absence of prey (van Rijn et al 2002).…”
Section: Introductionmentioning
confidence: 99%